National trends in extremity fracture hospitalizations among older adults between 2003 and 2017. Issue 9 (1st June 2021) - Reider, Lisa; Pollak, Andrew; Wolff, Jennifer L.; Magaziner, Jay; Levy, Joseph F.
Abstract: Background: Fractures in late life are highly consequential for health, services use, and spending. Little is known about trends in extremity fracture hospitalizations among older adults in the United States. Design: Retrospective longitudinal cohort study. Setting: The 2003–2017 National Inpatient Sample (NIS), a representative sample of U.S. community hospitals. Participants: Hospitalized adults aged 65 and older with a diagnosis of upper or lower extremity fracture. Measurements: Incidence of extremity fracture hospitalization and mortality, using NIS discharge and trend weights, and population denominators derived from the U.S. Census Bureau. Incidence was reported separately for men and women by age, fracture diagnosis, and injury mechanism. Weighted linear regression was used to test for significant trends over time. Results: Incidence of extremity fracture hospitalizations declined in both women (15.7%, p trend < 0.001) and men (3.2%, p trend < 0.001) between 2003 and 2017. This trend was primarily attributed to a decline in low energy femur fractures which accounted for 65% of all fracture hospitalizations. Among older adults with an extremity fracture hospitalization, mortality declined from 5.1% in 2003 to 3.3% in 2017 in men, and from 2.6% to 1.9% in women ( p trend < 0.001). High energy fractures were due to falls (53%), motor vehicle accidents (34%), and other high impact injuries (13%). Overall, 12% of extremity fracture hospitalizations were attributed to high‐energy injuries: increases were observed among men ages 65–74 (20%; p trend < 0.001) and 75–84 (10%; p trend = 0.013), but not among women of any age. Conclusion: Observed declines in the incidence of extremity fracture hospitalizations and related mortality are encouraging. However, increasing incidence of fracture hospitalization from high energy injuries among men suggests that older adults with complex injuries will be seen with more prevalence in the future.